La suprématie législative et l'édiction d'une charte des droits britannique - Tremblay, Guy; Bellavance, Sylvain (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1988)
The purpose of this article is to demonstrate that the enactment of a Bill of Rights in the United Kingdom is probable but that the constitutional entrenchment of the rights involved is not contemplated. It is submitted that the model proposed for the United Kingdom is very appropriate in a democratic society. The bills which are analysed incorporate international standards in British law, they operate upon Acts of Parliament and they preserve a normal margin of discretion for the political branches of the State. The authors conclude that in Canada the protection of fundamental rights has been more technicalized and that we should pause and reevaluate our approach in this respect. In particular, the repeal of section 33 of the Canadian Charter — which permits express exceptions to certain rights — would be a step in the wrong direction.